The Holocene stratified screes from Sierra de Albarracín (Iberian Ranges, Spain) and their paleoenvironmental significance - Peña Monné, José Luis (2017)
The most important stratified screes of the Iberian Range are found in Sierra de Albarracín. These slope deposits have been traditionally considered, without absolute datings, as having been formed during various Pleistocene cold phases. The aim of this paper is to establish the sedimentological, morphological, chronological, and paleoenvironmental characteristics of these deposits through the study of four profiles recorded in the Calomarde canyon (El Rollo, El Molino, and Royuela) and Toril. The most representative profile is that of El Rollo as it is formed by basal tufa and stratified scree layers separated by paleosoils. Radiocarbon datings obtained from paleosoil samples show that the sequence ranges between the early and middle Holocene. The profiles from El Molino and Royuela, as well as the upper levels of Toril, complete the sequence showing deposits from upper Holocene (Bronze Age and ‘Little Ice Age’). These data show the oscillations during the Holocene between colder phases, represented by the stratified screes, and warmer–wetter phases with soil development and local tufa deposits. This geomorphological and pedological response to the Holocene climatic variability shows its clearest records in the canyons. However, there are almost no Pleistocene accumulations – with the exception of that of Toril (minimum age of <43.5 ka BP). The possibility of relating this succession of Holocene environmental changes to known regional and global climatic stages converts these accumulations into the most important Holocene paleoenvironmental record from the Iberian Ranges and the most complete sequence of Holocene stratified screes from the Mediterranean area.